TECHNICAL SOLUTIONS TO IMPROVE THE PERFORMANCE AND UTILISATION OF PUMPING EQUIPMENT - Kurbonov Oybek Muhammadqulovich; To'xtashev Alisher Baxodirovich; Istamov Zafarjon Vohid o'g'li; Abdixakimova Malika Amir qizi (Web of Journals Publishing, 2025)
The article studies methods and ways of increasing the efficiency of submersible pumps, as well as modernisation of structural elements of their control means to increase the efficiency and utilisation rate of pumping equipment using innovative technical solutions of Grundfos company.
Keywords: Pump, efficiency, electric motor, electronic device, solution level.